Lexemes with the “camel” component in Kazakh: problems of translation - Zhumay, Nurmira; Jadira Аbibullaevna Zhunissova, Saiyn ZhaziraGulbakram Tumarbekovna Zhiyembayeva Maira Abibullaevna Zhunissova, (Opción, 2020)
The article is devoted to the analyses of the units with the camel component which are reflected in the short stories of the Kazakh writer Oralkhan Bokey via a comparative analysis of texts, including the text of Kazakh and the texts of translated languages. As a result, Oralkhan Bokey’s masterpieces in Kazakh literature are unusual and not like other writers’ works surprising with his dissimilarity. In conclusion, in the Kazakh language, to indicate various signs of the same object, phenomenon, or condition separate lexemes are used.